2015
DOI: 10.1063/1.4930800
|View full text |Cite
|
Sign up to set email alerts
|

Quantum mechanical derivation of the Wallis formula for π

Abstract: A famous pre-Newtonian formula for π is obtained directly from the variational approach to the spectrum of the hydrogen atom in spaces of arbitrary dimensions greater than one, including the physical three dimensions.The formula for π as the infinite product (1) that originates in physics, specifically in quantum mechanics. It is the purpose of this paper to show that this formula can in fact be derived from a variational computation of the spectrum of the hydrogen atom. The existence of such a derivation indi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…The HNH is based on pure integer mathematical properties. It has recently been shown that π/2 can be derived from the orbital energy levels seen in the hydrogen atom [34]. We have shown that it is possible to the first approximation derive the properties of hydrogen from the frequency of the neutron only in conjunction with the prime numbers 2, 3, 5, 7, 11 [30].…”
Section: Assignment Of a Partial Harmonic Fraction 1/2 To ν Cmbmentioning
confidence: 91%
“…The HNH is based on pure integer mathematical properties. It has recently been shown that π/2 can be derived from the orbital energy levels seen in the hydrogen atom [34]. We have shown that it is possible to the first approximation derive the properties of hydrogen from the frequency of the neutron only in conjunction with the prime numbers 2, 3, 5, 7, 11 [30].…”
Section: Assignment Of a Partial Harmonic Fraction 1/2 To ν Cmbmentioning
confidence: 91%
“…π has an infinite number of digits in its decimal representation and no repeating pattern ever occurs. Magically, the formula for π appears in a basic calculation in the physics of the hydrogen atom (Friedmann and Hagen 2015). Then there is the claim that the distribution of the prime numbers follow the energy levels of a quantum system (Bender et al 2017).…”
Section: )mentioning
confidence: 99%
“…In the recent article [1] the authors claim that a venerable asymptotic formula for π, the Wallis (1655) product, is related to quantum mechanics. More precisely to the variational method applied to the ground state of the hydrogen atom in the limit of large angular momentum (the classical limit ℓ → ∞).…”
Section: Introductionmentioning
confidence: 99%
“…So perhaps there are other potentials and trial functions that can give rise to the Wallis asymptotic formula for π or variants of it. The classical limit that we will take is just the classical limit used in [1].…”
Section: Introductionmentioning
confidence: 99%